STUDENTS’ PERCEPTIONS TOWARDS THE IMPLEMENTATION OF EFL MULTICULTURAL-BASED READING ACTIVITIES IN A HIGHER EDUCATION SETTING - Amrih Bekti Utami (IAIN Syekh Nurjati Cirebon, 2024)
This research study explores first-year university students’ perspectives on integrating multicultural-based reading activities into their EFL reading courses during their second semester. The researcher used a qualitative methodology to collect detailed data, including semi-structured interviews as the primary data, as well as focus group discussions, field notes, and classroom artifacts, from 40 undergraduate students majoring in the English Language Education Department at a public university in Yogyakarta, Indonesia. The data gained were analyzed and interpreted qualitatively by using thematic analysis, particularly the interview and field notes taken during the implementation of the activity, to reveal several key findings. Two major different themes were finally concluded: cultural awareness, and critical thinking skills. It was found that students became more involved, understood better, and respected other cultures. Besides, they elaborated on their critical thinking skills by interpreting and evaluating the texts. The results of the study posit further research to investigate how the activities may affect students’ language skills in communicating with people from different cultures in the long term.